2019
DOI: 10.3389/fimmu.2019.01482
|View full text |Cite|
|
Sign up to set email alerts
|

Rheumatoid Synovial Fluids Regulate the Immunomodulatory Potential of Adipose-Derived Mesenchymal Stem Cells Through a TNF/NF-κB-Dependent Mechanism

Abstract: Introduction: Adipose-derived mesenchymal stem cells (ADSC) have been shown to have remarkable immune-modulating effects. However, their efficacy in clinical trials has yet to be fully demonstrated. This could be due to a lack of a proper inflammatory environment in vivo that primes ADSC. Here, we define how the articular microenvironment of rheumatoid arthritis (RA) patients modulates the therapeutic efficiency of ADSC. Methods: Synovial fluids (SF) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 42 publications
(48 reference statements)
3
30
0
Order By: Relevance
“…As already reported [ 29 31 ], osteoarthritic synovial fluid influences the expression of molecules involved in immunomodulation. Furthermore, Sayegh et al recently demonstrated that coculture of AMSCs exposed to SF of patients affected by rheumatoid arthritis (RA), with activated monocyte or CD4+ cells, can inhibit the expression of CD40 and CD80 (monocyte's proinflammatory markers) and promote T reg expansion [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…As already reported [ 29 31 ], osteoarthritic synovial fluid influences the expression of molecules involved in immunomodulation. Furthermore, Sayegh et al recently demonstrated that coculture of AMSCs exposed to SF of patients affected by rheumatoid arthritis (RA), with activated monocyte or CD4+ cells, can inhibit the expression of CD40 and CD80 (monocyte's proinflammatory markers) and promote T reg expansion [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…ASDCs' response was altered upon treatment with synovial fluids from patients suffering from RA and coculture with macrophages or T-cells, further proving that the local environment influenced ASCs. Further analysis is required to clarify the immunomodulatory potential of ASCs and fully take advantage of their clinical benefit [56].…”
Section: Tissue Regeneration Researchmentioning
confidence: 99%
“…NF-κB regulates periodontal inflammation and the pathophysiology of periodontitis ( Francis et al, 2020 ). TNF/NF-κB signaling also plays a role in the pathophysiology of various inflammatory diseases ( Liedtke and Trautwein, 2012 ; Kunz, 2013 ; Sayegh et al, 2019 ). mRNA sequencing of LPS-treaded macrophages from anti-Act1 mice showed upregulation of TNF/NF-κB signaling related genes, including Tnfα, Il-1β, Ccl2, and Nfkbia.…”
Section: Discussionmentioning
confidence: 99%